Outcomes among scalp psoriasis patients: Is scalp psoriasis resistant to topical treatment? - Toral S Vaidya; Michael E Farhangian; Kathryn L Anderson; Alyson Snyder; Steven R Feldman (Wolters Kluwer Medknow Publications, 2018)
Background: Scalp psoriasis is considered notoriously difficult to treat, despite good percutaneous absorption of topical corticosteroids through scalp skin. Poor adherence to treatment is often the cause of poor treatment outcomes. Purpose: Our objective was to gain preliminary assessments of scalp psoriasis treatment outcomes from our patients' perspectives and to assess the feasibility of telephone-based follow-up of scalp psoriasis treatment. Methods: Chart review identified adults seen for scalp psoriasis in the past 3 years. Thirty patients were queried regarding their current disease state, treatment satisfaction, and whether they called the office to report disease progress. Results: Eight-seven percent of the patients reported "doing well" or "moderate improvement;" of these patients, 69% were on only one topical treatment. 90% were on topical treatments alone; of these patients, 93% reported "doing well" or "moderate improvement." Three of 15 patients who were told to call their provider and report treatment progressfollowed the instruction; those 3 reported "doing well." Patients given a simple topical corticosteroid treatment regimen and encouraged to report their progress to achieve at least moderate improvement. Conclusions: The dogma that scalp psoriasis treatments are resistant to treatment should be reassessed and larger controlled trials should be done to develop and test adherence interventions to improve scalp psoriasis outcomes.